Bahasa Inggris beraksen Asia: Persepsi mahasiswa - Ramadhani, Siffa Annisa Fitri; Siti Wahida; Nina Listiana (JURNAL PENDIDIKAN DAN SAINS, 2024)
The shift of English as a Lingua Franca (ELF) has directed to the need of deeper exploration in the acceptance of English varieties, especially Asian English varieties. This study aimed at investigating students’ perceptions toward Indian English in communication and teaching and learning. Using mixed-method explanatory story, this study collected the data by administering a questionnaire to 20 students enrolled in a listening class and 3 of them voluntarily participated in semi-structured interview. This study revealed that the students view Indian English as friendly, interesting, clear and competent accent. They also accepted the variety in communication. However, there is still a strong tendency of nativeness. The students highly value native-like sound when they speak English. Reflecting on the findings, it is recommended to expose different English varieties, especially Asian English varieties to prepare students with real-life communication. It is also worth pointing to conduct studies in Asian English, not only the accents but also its availability in a learning process.